2000
DOI: 10.1142/s0218127400000098
|View full text |Cite
|
Sign up to set email alerts
|

Stable Oscillations and Devil's Staircase in the Van Der Pol Oscillator

Abstract: A forced van der Pol relaxation oscillator is studied experimentally in the regime of stable oscillations. The variable parameter is chosen to be the driving frequency. For a range of parameter values, we show that the rotation number varies continuously from 0 to 1. This work provides experimental evidence that period-adding bifurcations to chaos previously reported by Kennedy and Chua are intimately connected to the existence of a regime of stable oscillations where the rotation number shows a Devil's-stairc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…In the van der Pol oscillator, both routes – period-adding [83], [100] and period-doubling cascades – occur [91], [101]. On the other hand, our results concerning the route to chaos are in line with findings in a periodically stimulated excitable neural relaxation oscillator [27] and a simple model of the Belousov-Zhabotinsky reaction [102].…”
Section: Discussionsupporting
confidence: 90%
“…In the van der Pol oscillator, both routes – period-adding [83], [100] and period-doubling cascades – occur [91], [101]. On the other hand, our results concerning the route to chaos are in line with findings in a periodically stimulated excitable neural relaxation oscillator [27] and a simple model of the Belousov-Zhabotinsky reaction [102].…”
Section: Discussionsupporting
confidence: 90%
“…(1) is promoted to three dimensions the relaxation oscillation dynamics becomes much richer to include oscillations of multiple periodicities, almost periodic solutions, coexisting or multistable periodic solutions as well as regions of chaos. This is achieved, as mentioned above, by introducing in time a periodic forcing term to the right-hand side of van der Pol's equation, the object of many studies up to the present day [Gilbert & Gammon, 2000]. Arneodo et al [1985] demonstrated self-generated multiple periodicities, and chaos is displayed by a third-order differential equation linear in the velocity but supplemented by a quadratic nonlinearity in the x-coordinate.…”
Section: Discussionmentioning
confidence: 99%
“…The coexistence of OMO and SOM mechanisms adds extra degrees of freedom to the dynamic space of system and results in increased susceptibility to destabilization (detailed in Supplementary Note 2 ) 16 18 21 .When the drive power is between the SOM and OMO thresholds, TPA-associated amplitude modulations disrupt the OMO rhythm, breaking the closed OMO limit cycles and creating the non-repeating chaotic oscillations. On the other hand, if the frequency ratio between OMO and SOM is close to a rational value, they will lock each other based on the harmonic frequency locking phenomena 39 40 . Consequently, different sub-harmonic f omo states are also observed in Fig.…”
Section: Resultsmentioning
confidence: 99%